Analysis of Effectiveness of Discovery Learning Model in Science Learning Activities for Basic Students - Iskandar, Suhendra (Jurnal Pijar Mipa, 2025)
Unlike other learning models, the Discovery Learning model emphasizes theoretical and practical in-depth material exploration, ensuring no learning objectives are overlooked. This differs from other student-centred learning (SCL) models, which grant full autonomy to students. The Discovery Learning model incorporates the role of lecturers as assistants, allowing students to build a strong foundational understanding of knowledge.  This study investigates the effectiveness of the Discovery Learning model in science learning for students of the Madrasah Ibtidaiyah Teacher Education program at IAIN Sultan Amai Gorontalo. The research was conducted through four cycles, each consisting of the learning steps of stimulation, problem identification, data collection, data processing, verification, generalization, and reflection. The success of the learning activities was measured by improvements in learning outcomes, reflected in the scores of pre-tests conducted before implementing the learning model and post-tests conducted afterwards.  The hypothesis was tested using the paired-sample test to determine the significance between pre-test and post-test scores in each cycle, followed by an effectiveness test using the N-gain test. The findings confirmed the hypothesis, as all cycles showed a t-value greater than the critical t-table value, indicating increased learning outcomes through the Discovery Learning model. This was also evident in the consistent improvement in the average scores between pre-tests and post-tests in each cycle. However, based on the N-gain test, the effectiveness of the learning model was found to be only 53.35%, which falls into the category of low effectiveness. This suggests a need for additional scientific literature and laboratory equipment within the scope of IAIN Sultan Amai Gorontalo.